An improved spatial subsidy approach for ecological compensation in coastal seascapes for resilient land-sea management. (15th December 2020) - Li, Yangfan; Xiang, Zhiyuan; Chen, Keliang; Wang, Xianyan
Abstract: Human activities are considered a critical impact factor for decision-making in coupled human-nature systems, such as conservation of coastal systems. Identifying key human activities that cause significant habitat degradation for coastal species remains challenging. We improved the spatial subsidy approach to identify and prioritize control strategies for human-caused distribution shifts of marine species. We applied this method to a threatened Indo-Pacific humpback dolphin ( Sousa chinensis ) in Xiamen Bay, China. Our results indicate that (1) a significant distribution shift for humpback dolphins from existing nature reserves to peripheral waters occurred from 2011 to 2014; (2) coastal tourism and industrial and urban construction had more significant negative impacts on humpback dolphins than maritime transportation and reclamation; and (3) proactive management should be implemented for maritime transportation and reclamation, while reactive management should be implemented for coastal tourism and industrial and urban construction. Human impact analysis, combined with spatially explicit modeling, contributes to determining the spatial alternatives for conservation planning. In response to possible ecological damage caused by human activities, the improved spatial subsidy results help provide knowledge and platforms for ecological compensation. Highlights: Trade-off values are used to develop spatial subsidies for humpback dolphins. Human impacts prevent an existing nature reserve from covering the dolphins' home. Tourism and construction need to pay more for the conservation of humpback dolphins.